Vestiges Of The World’s Bane: The Threat Of ISIS Resurgence Amidst The Turbulence In Postwar Syria - Ramadhany, Ghifarie Aulia; Manullang, Abel Josafat (PT. Student Rihlah Indonesia, 2025)
Some of the leftover from conflict such as unresolved status of ISIS-linked detainees, including women and children held in overcrowded and poorly managed facilities such as Al-Hol camp, continue to pose pressing humanitarian and security risks. This study aims to analyze the implications of prolonged detention on regional stability and radicalization efforts. By using a qualitative descriptive method, the research utilizes purposive sampling of secondary data from 2015–2024, which includes academic works, NGO and UN reports, and journalistic investigations. Our findings reveal that legal ambiguity, substandard living conditions, and lack of adequate oversight create a volatile environment that may deepen the spread extremist ideologies. The study also explores the role of geopolitical dynamics, especially Turkey’s involvement in northern Syria and the questions involving Kurdish groups. The paper contributes to current discourse by offering a unique approach of the ISIS remnant issue in postwar Syria. The authors emphasize the need for a coordinated international policy response, urging the need for detainee rights protection, rehabilitation efforts, and sustainable reintegration programs within the region.